Analysis Limiting Internet Sites With The Method Using Squid Proxy Server At SMKN 1 South Rawajitu - Reni Tri Astuti (Bandar Lampung University (UBL), 2014)
SMKN 1 South Rawajitu is one of the vocational schools are housed in Tulang Bawang. Because the local computer network is the most important thing being facilities in the Department of Computer Engineering and Networks to perform activities of daily practice, then the SMKN 1 South Rawajitu give fasillitas LAB into local networks available in the CMS. But the length of Internet use, the frequent misuse, because the user is in SMKN 1 South Rawajitu, especially students at SMKN 1 South Rawajitu often do access to sites that are prohibited to be accessed when hours of lessons such as social media sites facebook and to anticipate access to porn sites or by surfing unhealthy. Solutions that can be done is to build a proxy server by utilizing the existing facilities such as open source, especially Linux debian linux, linux application, there is one application that can narrow web application that is using squid. The use Squid proxy server with linux is more efficient because in addition to assemble their own servers and make low cost, the server is also not lose performance with servers who paid a heavy price.